2011
DOI: 10.1016/j.jvs.2010.11.105
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous endovenous treatment of congenital extratruncular venous malformations with an ultrasound-guided and 810-nm diode laser

Abstract: Treatment of congenital EVMs with endovenous laser ablation under US guidance achieved palliation in most symptomatic patients; it was safe, with minimal morbidity during short-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…The immediate results indicated an excellent closure rate of 100% comparing favorably to other minimally invasive techniques. These results were confirmed by other groups [107,[110][111][112][113]. A study of the short-term efficacy of EVLT showed that 99% out of 90 cases still showed vessel closures after 9 months follow-up [107].…”
Section: Treatment Of Vascular Malformations and Hemangiomas With Diosupporting
confidence: 66%
“…The immediate results indicated an excellent closure rate of 100% comparing favorably to other minimally invasive techniques. These results were confirmed by other groups [107,[110][111][112][113]. A study of the short-term efficacy of EVLT showed that 99% out of 90 cases still showed vessel closures after 9 months follow-up [107].…”
Section: Treatment Of Vascular Malformations and Hemangiomas With Diosupporting
confidence: 66%
“…Sidhu et al . and Lu et al . reported alleviation of pain in all 8 and 51 lesions in 6 and 33 patients, respectively.…”
Section: Resultsmentioning
confidence: 92%
“…High laser energy levels can destroy the PTFE and Dacron fabrics completely, which might limit the potential ischemia time to <2 minutes during operations. The diode laser was used to treat superficial venous insufficiency and congenital extratruncular venous malformations, as we recently reported . The diode laser was developed to obtain a more selective action against blood vessels than previous lasers, which operate at wavelengths of 940 or 810 nm, with selective tertiary hemoglobin peak, and a depth of penetration in the blood of just 0.3 mm .…”
Section: Discussionmentioning
confidence: 99%